Prognostic significance of diffuse sclerosing variant papillary thyroid carcinoma: a systematic review and meta-analysis. Issue 4 (April 2017) - Vuong, Huy Gia; Kondo, Tetsuo; Pham, Thong Quang; Oishi, Naoki; Mochizuki, Kunio; Nakazawa, Tadao; Hassell, Lewis; Katoh, Ryohei
Abstract : Objective: Diffuse sclerosing variant papillary thyroid carcinoma (DSVPTC) is an uncommon variant of papillary thyroid carcinoma (PTC). The biological behaviors and prognostic outcomes of this variant, however, are still controversial. The aim of this systematic review and meta-analysis is to investigate the prognostic significance and outcomes of DSVPTCs in comparison with classical PTCs (cPTCs). Methods: An electronic search was performed in five libraries: PubMed, Scopus, ISI, World Health Organization Global Health Library (WHO GHL) and Virtual Health Library (VHL) in June 2016. Published data were extracted and were pooled into odds ratios (OR), mean differences and corresponding 95% confidence intervals (CI) using random-effect model. Publication bias was analyzed using Egger's regression test and funnel plot observation. Results: From 315 articles, we included 16 articles comprising 732 DSVPTCs for meta-analysis. Overall, DSVPTC manifested more aggressive clinicopathological behaviors than cPTC such as higher rate of vascular invasion (OR: 5.33; 95% CI: 3.08–9.23), extrathyroidal extension (OR: 2.96; 95% CI: 2.04–4.30), lymph node metastasis (OR: 5.40; 95% CI: 2.82–10.35), distant metastasis (OR: 3.61; 95% CI: 1.89–6.88) and were more likely to relapse (OR: 2.83; 95% CI: 1.59–5.05). DSVPTC patients were associated with a worsened overall survival (HR: 1.89; 95% CI: 1.36–2.62). Conclusion: DSVPTCs should be considered high-risk PTCs because of high propensity for tumor invasion, metastasis, relapse and mortality. Aggressiveness of DSVPTCs might be related to a different molecular pathway than that in cPTCs.